Socioeconomic perception and knowledge of the consumption of Ablo, a cereal food fermented of Benin - BANON, Jultesse; BOKOSSA YAOU, Innocent Padonou; TCHEKESSI, C. K. Célestin; SACHI, Amour Pivot; DJOGBE, Anayce A. Mikponsè; BLEOUSSI, Tchèlissa Myriam Roseline; MENSAH, GUY APOLLINAIRE (My University, 2016)
The Ablo is a cereal food fermented. It is considered like a humid, slightly, salty and sugary bread, cooked steam and sold under shape of ball. The objective of the survey is to have present quantitative and qualitative data on the consumption of Ablo in Benin. The methodology adopted to consist in doing an investigation of land in some townships of the center (Abomey, Bohicon, Covè) and of the south (Abomey-Calavi, Comè, Cotonou) Benin by the consumers of Ablo. The results of our investigations showed that the Ablo is a food descended of the informal sector of street food. The consumers of Ablo are of all age and all socio-professional catégory. The consumers are of three categories to know the population, the promoters of feast and the hotels and restaurants. The Ablo is consumed to the snack for the majority and is served to hot accompanied of pimento or frying more of fish or meat fried.
Keywords: Ablo; Benin; investigation; socio-economy; consumption.